The Benefits of Reading Aloud for Children: A Review in EFL Context - Jennet Senawati; Ni Komang Arie Suwastini; I Gusti Agung Sri Rwa Jayantini; Ni Luh Putu Sri Adnyani; Ni Nyoman Artini (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTAlthough reading aloud is an old teaching strategy, its relevance has been vouched by research from time to time. The present study aimed to critically review experts' opinions and results of previous research on the definition and characteristics of reading aloud and its benefits for young children in the EFL contexts by employing George’s (2008) model of literature review. The review revealed that the teacher plays the most crucial role in reading aloud, acting as the bridge between the text and the student's comprehension. A good design of reading aloud demands the teacher’s competence in choosing the text to meet the students’ interest and level; planning the tempo of the reading and the pauses to pose questions and comments; and making connections with the text and the children. Reading aloud benefits children’s English regarding their vocabulary, pronunciation, comprehension, listening skills, reading skills, speaking skills, communicative skills, and motivation, literacy, and critical thinking skills. These results imply that reading aloud is still relevant to be implemented nowadays because of the benefits it brings to children’s English. ABSTRAKMeski sering dianggap metode lama, membaca nyaring memberi banyak manfaat. Artikel ini bertujuan untuk melakukan kajian kritis terhadap pendapat ahli dan penelitian terdahulu mengenai pengertian, ciri khas, serta manfaat membaca nyaring, dengan mengikuti model penelitian kajian pustaka George (2008). Diungkapkan bahwa guru menjadi penentu kesuksesan kegiatan membaca nyaring sebagai jembatan yang menghubungkan siswa dengan teks yang dibaca. Kegiatan membaca nyaring bergantung pada kemampuan guru untuk memilih teks yang sesuai dengan minat dan kemampuan siswa, serta merancang proses pembacaan terkait tempo dan penempatan jeda untuk memberi komentar, bertanya, maupun membuat kaitan-kaitan antara teks dan siswa. Ahli dan penelitian terdahulu berpendapat bahwa kegiatan membaca nyaring berkontribusi secara positif terhadap siswa terkait pembentukan kosakata, pelafalan, pemahaman, keterampilan mendengar, membaca, berbicara, dan berkomunikasi, serta motivasi, literasi, dan kemampuan berpikir kritis berkomunikasi mereka. Jadi, membaca nyaring sangat relevan diimmplementasikan pada jaman sekarang karena kegiatan ini sangat positif untuk perkembangan Bahasa Inggris siswa.